Surgical Atlas of Cardiac Anatomy - Zhu, Xiaodong (Springer Netherlands : Imprint: Springer, 2015)
This Atlas is illustrated with rich pictures of cardiac surgical specimens. It not only contains normal heart specimens but also dissects those specimens, taking pictures from various angles to create a three-dimensional representation. It also includes reviews of the specimens' pathological reviews. Chapter 1 through 10 introduce the normal anatomy of the cardiac chambers and surgical approaches to the heart, while chapter 11 through 28 describe 18 kinds of congenital heart defects. There are a total of over 1,000 images and illustrations in this book, which will be of great interest not only to the surgeons, but also to the cardiologists, anaesthesiologists and surgical pathologists. Editor Xiaodong Zhu is professor and former dean of Fuwai Hospital, Chinese Academy of Medical Science and Peking Union Medical College. He is an academician of the Chinese Academy of Engineering.